Corrigendum to “Pb removal from water by three types of biofilters”. [Journal of Trace Elements and Minerals 2C (2022) 100027](S277305062200026X)(10.1016/j.jtemin.2022.100027) - Bordon, Isabella C. [UNESP]; Campos, Bruno G. [UNESP]; Miyai, Caio A. [UNESP]; Silva, José Roberto Machado Cunha da; Cotrim, Marycel E.B.; Favaro, Deborah I.T.; Abessa, Denis M.S. [UNESP] (Elsevier, 2024)
The authors regret that Ethical Statement and Editor Conflict of Interest are missing which is appended below:Ethical StatementThe authors declare that they have no known reports on human studies, especially those involving placebo, symptom provocation, drug discontinuation, or patients with disorders that may impair decision-making capability reported in this paper.Editor Conflict of InterestGiven their role as [Editorial Board Member/Editor/Editor-in-Chief], they had no involvement in the peer-review of this article and has no access to information regarding its peer-review. The authors would like to apologise for any inconvenience caused.